2011
DOI: 10.1007/s10549-011-1510-6
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor polyglutamine tract length in Egyptian male breast cancer patients

Abstract: Male Breast Cancer (MBC) is a rare disease in the U.S., accounting for less than 1% of all breast cancers. Rates of MBC in Africa are more variable than in the U.S., therefore, understanding the risk factors involved in a population like Egypt can clarify the nature of MBC. The polyglutamine tract (QT) is a variable region of the androgen receptor (AR), a nuclear receptor which is important in modulating androgen actions and generally inhibits growth in breast tissue. It is hypothesized that a long QT results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Two studies searching for an association between CAG repeat length and MBC did not notice any appreciable differences between cases and the respective control groups [22,25]. Two other studies suggested that longer CAG repeats are more common in MBC that in controls [26,27], and a trend toward a higher frequency of shorter CAG tracts in the control group emerged from a fifth report [28]. Thus, even though genetic evidence is scarce and somewhat ambiguous, the scenario proposed is that androgen hyposensitivity caused by either AR mutations or long CAG repeats might be a causal factor for MBC.…”
Section: Ar In Mbc: Genomicsmentioning
confidence: 97%
“…Two studies searching for an association between CAG repeat length and MBC did not notice any appreciable differences between cases and the respective control groups [22,25]. Two other studies suggested that longer CAG repeats are more common in MBC that in controls [26,27], and a trend toward a higher frequency of shorter CAG tracts in the control group emerged from a fifth report [28]. Thus, even though genetic evidence is scarce and somewhat ambiguous, the scenario proposed is that androgen hyposensitivity caused by either AR mutations or long CAG repeats might be a causal factor for MBC.…”
Section: Ar In Mbc: Genomicsmentioning
confidence: 97%
“…CAG repeat length data on the Moroccan patients were not available because of the limited amount of tissues available for this study. However, in previous studies, it has been seen that short CAG repeat lengths are more prevalent among non-MBC controls compared to MBC patients [20,48]. It should also be noted that our study’s finding of CAG repeat lengths of Egyptian MBC patients (19.5 ± 2.8) and controls (19.3 ± 4.2) are in agreement with a previous study that found an average CAG repeat length of 18.18 ± 3.63 for healthy Egyptian men [2].…”
Section: Discussionmentioning
confidence: 99%
“…PCR amplification of isolated patient DNA followed by fragment length analysis according to the methods described by Gilbert et al, 2011, reveal the number of CAG repeats in this region. A case-control study comparing the CAG repeat lengths in the 44 Egyptian MBC tumor and 43 non-MBC controls found no significant difference in amount of repeats (MBC cases: 19.5 ± 2.8 repeats, Controls: 19.3 ± 4.2 repeats, P = 0.843), but did note a higher proportion of short repeat lengths among controls, possibly suggesting a protective effect of short CAG repeat lengths [20]. A similar case-control study of the androgen receptor CAG repeat length was not done with the Moroccan samples due to the limited amount of tissues available.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…100 ng of DNA was amplified in a reaction mix containing 1 µl of each primer at 10 pmol, 0.8 µl 50 mM MgCl 2 , 0.2 µl Platinum® Taq DNA polymerase (Life technologies Invitrogen, USA), 10 µl of Gene Amp Fast PCR Mix from ABI (Applied Biosystems, USA), and distilled water to bring to final volume to 25 µl. PCR was performed according to a standard protocol (modified from Gilbert SF [6]); starting with 94°C for 2 min; followed by 30 cycles of 94°C denaturation for 30 s, 55°C annealing for 30 s, and 72°C extension for 1 min; ending with a final extension at 72°C for 30 min. Digital images of fluorescent gel data were acquired using Data Collection Software and analyzed using GeneScan Software (both from Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%